Protein Kinase C δ Mediates Cerebral Reperfusion Injury In Vivo - Bright, Rachel (J Neurosci, 2004)
Protein kinase C (PKC) has been implicated in mediating ischemic and reperfusion damage in multiple organs. However, conflicting reports exist on the role of individual PKC isozymes in cerebral ischemic injury. Using a peptide inhibitor selective for δPKC, δV1-1, we found that δPKC inhibition reduced cellular injury in a rat hippocampal slice model of cerebral ischemia [oxygen-glucose deprivation (OGD)] when present both during OGD and for the first 3 hr of reperfusion. We next demonstrated peptide delivery to the brain parenchyma after in vivo delivery by detecting biotin-conjugatedδV1-1 and by measuring inhibition of intracellular δPKC translocation, an indicator of δPKC activity. Delivery of δV1-1 decreased infarct size in an in vivo rat stroke model of transient middle cerebral artery occlusion. Importantly, δV1-1 had no effect when delivered immediately before ischemia. However, delivery at the onset, at 1 hr, or at 6 hr of reperfusion reduced injury by 68, 47, and 58%, respectively. Previous work has implicated δPKC in mediating apoptotic processes. We therefore determined whether δPKC inhibition altered apoptotic cell death or cell survival pathways in our models. We found that δV1-1 reduced numbers of terminal deoxynucleotidyl transferase-mediated biotinylated UTP nick end labeling-positive cells, indicating decreased apoptosis, increased levels of phospho-Akt, a kinase involved in cell survival pathways, and inhibited BAD (Bcl-2-associated death protein) protein translocation from the cell cytosol to the membrane, indicating inhibition of proapoptotic signaling. These data support a deleterious role for δPKC during reperfusion and suggest that δV1-1 delivery, even hours after commencement of reperfusion, may provide a therapeutic advantage after cerebral ischemia.